Book ReviewsRittiR. R.FunkhouserG. Ray. The Ropes to Skip and the Ropes to Know (Grid Inc., 1977), 252 pp., paperback $5.95. - Klein, Stuart M. (Academy of Management Review, 1977)
This article presents a review of the book ?The Ropes to Skip and the Ropes to Know,? by R. R. Ritti and G. Ray Funkhouser.